2018
DOI: 10.2147/dmso.s165967
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of major lower limb amputation in type 2 diabetic patients referred for hospital care with diabetic foot syndrome

Abstract: PurposeThis study was conducted to determine the risk factors of major lower extremity amputations in type 2 diabetic patients referred for hospital care with diabetic foot syndrome.Patients and methodsThis retrospective study involved 225 type 2 diabetic patients referred for management of diabetic foot syndrome at King Abdullah University Hospital in the period between January 2014 and December 2015. A structured customized diabetic foot data collection form with diabetic foot characteristics chart was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 38 publications
(77 reference statements)
3
45
0
3
Order By: Relevance
“…Interestingly, all dialysis‐dependent patients undergoing lower limb amputation also had concurrent diabetes . Multiple studies have concluded that patients requiring dialysis are at higher risk than the general population for MLLA, and this study confirms that in our cohort . It has also been suggested that there is a correlation between the severity of chronic kidney disease and amputation, which may be independent of clinically apparently peripheral artery disease …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, all dialysis‐dependent patients undergoing lower limb amputation also had concurrent diabetes . Multiple studies have concluded that patients requiring dialysis are at higher risk than the general population for MLLA, and this study confirms that in our cohort . It has also been suggested that there is a correlation between the severity of chronic kidney disease and amputation, which may be independent of clinically apparently peripheral artery disease …”
Section: Discussionsupporting
confidence: 87%
“…27 Multiple studies have concluded that patients requiring dialysis are at higher risk than the general population for MLLA, and this study confirms that in our cohort. [33][34][35] It has also been suggested that there is a correlation between the severity of chronic kidney disease and amputation, which may be independent of clinically apparently peripheral artery disease. 35 The rates of BKA in this study as a proportion of total MLLAs (62.7%) was comparable to other Australian cohorts, with Lim et al 15 reporting 58.6% and a study looking at 5 years' worth of data from all Australian states reporting 57.3%.…”
Section: Discussionmentioning
confidence: 99%
“…According to Pemayun et al, significant risk factors of LEA in their study included hypertension status (OR 2.85, 95% CI: 1.23‐6.60), presence of PAD (OR 6.80, 95% CI: 2.67‐17.32), presence of foot necrosis or gangrene (OR 25.88, 95% CI: 6.97‐96.13), FPG ≥ 126 mg/dL (OR 9.43, 95% CI: 1.13‐78.78), HbA1c ≥8% (OR 9.54, 95% CI: 2.03‐44.89), and triglycerides ≥150 mg/dL (OR 4.16, 95% CI: 1.75‐9.86); thus, good control of blood glucose and lipid levels and management of comorbidities such as PAD and hypertension are considered important factors in reducing amputation risk. According to a recent retrospective study by Shatnawi et al, higher HbA1c was also significantly associated with increased risk of major amputation (OR 4.0; 95% CI: 1.3‐12.4) in multivariate analysis, and diabetes duration longer than 15 years (OR 6.0), renal dysfunction (OR 3.5), and gangrene (OR 4.2) were also closely associated with increased risk of major amputation. A meta‐analysis by Zhou et al showed a statistically significant association between HbA1c and LEA risk (χ (2) = 65.51, P < .001), and the OR for LEA incidence was 1.229 (95% CI: 1.169‐1.292) for every 1% HbA1c increase in linear model; moreover, for HbA1c between 5% and 9%, the OR of LEA risk increased with HbA1c levels in the spline model.…”
Section: Discussionmentioning
confidence: 96%
“…Khalfallah et al reported that age was the only independent predictor for major lower‐extremity amputation (LEA) in DFU patients with a threshold age value of no less than 65 years in their study . In another study by Shatnawi et al, the presence of gangrenous tissues and uncontrolled blood glucose levels were significant predictive factors for type 2 diabetes‐related major LEA . The risk factors for LEA associated with diabetic foot diseases are extensive, including microvascular diseases, PAD, infections, long diabetes duration, poor glycaemic control, old age, and cardiovascular comorbidities .…”
Section: Introductionmentioning
confidence: 98%
“…Chronic wound patients have a reduced ability to undergo normal tissue repair and are more susceptible to ulcers, resulting in patient trauma, and often the need for limb amputation [1,2]. At present, chronic wounds impact four million Europeans per year, and at least 1% of people living in high economy countries will experience a complex wound in their lifetime [3,4].…”
Section: Introductionmentioning
confidence: 99%